1994
DOI: 10.1243/pime_proc_1994_208_104_02
|View full text |Cite
|
Sign up to set email alerts
|

Load Sharing in Metallic and Non-Metallic Gears

Abstract: A review of work o d o o t h deformatiohnd load sharing in non-metallic gears is presented. Ahnite element analys;&employing the flexibility method for contacting bodies is used to model tooth deflections and contact patterns 'Betweenheshing g e a r y For metallic gears the change in contact ratio between the theoretical and running values is shown to be small. However, for low modulus, non-Y t a l l i c gears the change in contact ratio is large and cangive cause for concern. The benefits and disadvantages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…In reference [15] the author included the gear body in his analysis, thereby reducing gear stiffness and compared the pitch point stiffness of gear pairs as determined by different authors. FE methods have been used for the analyses of polymer gears by Walton et al [16], who examined load sharing. As a result the real contact ratio as distinct from the ideal or theoretical contact ratio for spur gears was determined and plotted using a non-dimensional approach in which the real contact ratio was uniquely defined in terms of the gear geometry, torque and elastic modulus, termed the non-dimensional gear elasticity parameter.…”
Section: Gear Deformationsmentioning
confidence: 99%
“…In reference [15] the author included the gear body in his analysis, thereby reducing gear stiffness and compared the pitch point stiffness of gear pairs as determined by different authors. FE methods have been used for the analyses of polymer gears by Walton et al [16], who examined load sharing. As a result the real contact ratio as distinct from the ideal or theoretical contact ratio for spur gears was determined and plotted using a non-dimensional approach in which the real contact ratio was uniquely defined in terms of the gear geometry, torque and elastic modulus, termed the non-dimensional gear elasticity parameter.…”
Section: Gear Deformationsmentioning
confidence: 99%
“…Due to the large de�ections in polymer gears, real load sharing (and hence the real contact ratio) will be quite different to theoretical predictions [13]. Walton et al [14] suggested that the most severe conditions are likely to occur at the pitch point (which will be the same value for both theoretical and real conditions and so are representative of the most severe conditions).…”
Section: Elastohydrodynamic Lubricationmentioning
confidence: 94%
“…Note that in all the efficiency �gures shown in this paper, oil churning and spindle/bearing losses have been subtracted. Figure 7(b) shows the derived coefficients of friction calculated from the measured efficiencies and by using (14). While the coefficients of friction show the dependency of load, the curves are relatively �at with respect to speed.…”
Section: Experimental Programmementioning
confidence: 99%
“…The interference on the gear tooth profile after the last point of contact can be calculated as tip interference, Tf, and flank interference, Fi,. A finite element procedure has been adopted to calculate the deflection of gear teeth under load (14). In this work the authors were able to show that the real contact ratio, cR, could be expressed in terms of a non- @ IMcchE 1995 dimensional gear elasticity parameter, T = T/(rb bmE), and the ideal contact ratio, E, (Fig.…”
Section: Calculation Of Tip and Flank Interference By The Finite Elemmentioning
confidence: 96%